ANALISIS KINERJA KEUANGAN PEMERINTAH KOTA TANJUNG BALAI DALAM PENGELOLAAN APBD TAHUN ANGGARAN 2018-2022 - Gresi Lusina Br. Tobing; Lima Romaito Br. Situmorang; Zoyce Natalia Br. Tarigan; Eva Marlina Br. Sianturi; Hamonangan Siallagan; Rizki Christian Sipayung (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2023)
With regional autonomy, each region has the freedom to carry out its regional administrative activities as determined by the government. The right to autonomy is the basis for the Tanjung Balai City government in managing regional growth and development. Performance in this management can be seen in the Regional Revenue and Expenditure Budget. This study aims to determine the financial management performance of Tanjung Balai City during the period 2018 to 2022 which was studied using quantitative descriptive methods using regional financial ratios parameters such as the ratio of independence, effectiveness and efficiency ratios, growth ratios, decentralization degree ratios, and growth ratios. The results showed that the independence ratio was categorized in a participatory level of independence, the effectiveness ratio was classified as ineffective, the efficiency ratio was classified as efficient, the capital expenditure ratio was classified as low, the operating expenditure ratio was classified as high, the decentralization degree ratio was classified as low, the growth ratio consisting of the growth ratio of Regional Original Revenue (PAD), the ratio of regional income and the ratio of operating expenditure which was classified as low while the capital expenditure ratio was classified as high.